Microwave-assisted pyrolysis of vegetable oil soapstock: Comparative study of rapeseed, sunflower, corn, soybean, rice, and peanut oil soapstock - Wang, Yunpu; Zhang, Shumei; Wu, Qiuhao; Duan, Dengle; Liu, Yuhuan; Ruan, Roger; Fu, Guiming; Dai, Leilei; Jiang, Lin; Yu, Zhenting; et al. (International Journal of Agricultural and Biological Engineering, 2019)
In this study, the effects of catalytic temperature and the type of soapstock on products from microwave-assisted pyrolysis were investigated. HZSM-5 was used as the catalyst to study the pyrolysis of six different soapstocks at 200°C, 300°C, and 400°C catalytic temperature. Results showed that the bio-oil yields initially increased and then decreased with the increase in catalytic temperature. When the catalytic temperature was 300°C, the bio-oil reached up to the maximum value (65.8 wt.%). Findings indicated that the composition of bio-oil was related to the degree of unsaturation of fatty acids sodium in the soapstocks. In the case of saturated fatty acid sodium, a series of alkanes was formed, whereas the pyrolysis of monounsaturated fatty acid sodium resulted mainly in cycloalkanes, the cycloalkenes obtained from bio-oil was produced by polyunsaturated fatty acid sodium. Keywords: microwave pyrolysis vegetable oil soapstock, HZSM-5, bio-oil DOI: 10.25165/j.ijabe.20191206.4599 Citation: Wang Y P, Zhang S M, Wu Q H, Duan D L, Liu Y H, Ruan R, et al. Microwave-assisted pyrolysis of vegetable oil soapstock: Comparative study of rapeseed, sunflower, corn, soybean, rice, and peanut oil soapstock. Int J Agric & Biol Eng, 2019; 12(6): 202–208.